PENINGKATAN STATUS KESEHATAN JIWA KELUARGA YANG MEMILIKI ANAK RETARDASI MENTAL MELALUI PSIKOEDUKASI KELUARGA - Rosmaharani, Shanti; Rodiyah; I'in Noviana (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: This study aims to determine the effect of family psychoeducation on the mental health status of families with children with mental retardation Methods: The study used a pre-experimental design with a one-group pretest–posttest design. The study involved 45 families with children with mental retardation, using a total sampling technique. The independent variable was family psychoeducation, and the dependent variable was family mental health status. The intervention consisted of three sessions of family psychoeducation, each lasting 30–60 minutes. Family mental health status was measured using the Self-Reporting Questionnaire (SRQ-20) before and after the intervention. Data were analyzed using the Wilcoxon Signed Ranks Test. Results: The results showed that before the intervention, the majority of families (62%) were in the mild emotional disturbance category. After psychoeducation, the majority of families (67%) were in the normal category. The statistical analysis showed a p-value of 0.003 <0.005, indicating a significant effect of family psychoeducation on improving family mental health status. Conclusion: This study concluded that family psychoeducation is effective in improving the mental health status of families caring for children with mental retardation. This intervention is recommended for implementation in community psychiatric nursing services to improve family well-being and the quality of care for children with mental retardation.